De eerste inspecteurs van het middelbaar onderwijs. 'Het toezicht zal vooral op hem aankomen, het zal zijn onverdeelde zorg vorderen.' - Krüger, Jenneke (Studium, 2018)
The new Act on Secondary Education of 1863 contained a chapter on supervision of secondary schools. A system of local supervision by the council was combined with national supervision by a few inspectors. This paper discusses the work of the first three inspectors for secondary schools: Daniel Jan Steyn Parvé, Johannes Bosscha and Winand Staring.The inspectors were to visit all secondary schools, Higher Burger Schools (hbs) and others, to become and remain well-informed about the situation of those schools. They had additionally to stimulate the growth and the quality of secondary education and they were to inform and advise the Minister. Furthermore, the inspectors had an important role in the establishment of new schools, especially the hbs. During the first decades of the existence of the hbs they exerted a large influence on the development of the organisation and teaching of this new type of school. They had outspoken ideas on pedagogy, didactics, homework and other matters of relevance in education. Their influence had probably at least as much to do with their personalities as with their formal tasks.